Aplikasi Pintar : Hukum Tajwid Berbasis Android - Murad, Silvia Ayunda; Sujana, Dadang; Muhtyar, Ahmad (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
Information technology is now growing, the need for quality information is needed. The development of technology has a lot to influence the order of life or a certain rule and system that can be utilized in various fields, one of which is in the field of education. The system, which is summarized into an e-Learning concept, has an effect on the transformation of education into digital form both in content and systems. UNIS Tangerang has a faculty called the Science of Religion. One of the important subjects is understanding the use of recitation in the Koran. By using an applicative method, this research was built with the aim of making it easier for students to understand it and also making it easier for lecturers to transfer knowledge to students. With an interactive learning model, it is proven that the results are maximally measured by the passing scores of students in this course.